2023
DOI: 10.1101/2023.04.21.23287817
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Stage-dependent biomarker changes in spinocerebellar ataxia type 3

Abstract: Spinocerebellar ataxia type 3/Machado-Joseph disease (SCA3) is the most common autosomal dominant ataxia. In view of the development of targeted therapies for SCA3, precise knowledge of stage-dependent fluid and MRI biomarker changes is needed. We analyzed cross-sectional data of 292 SCA3 mutation carriers including 57 pre-ataxic individuals, and 108 healthy controls from the European Spinocerebellar ataxia type 3/Machado-Joseph Disease Initiative (ESMI) cohort. Blood concentrations of mutant ATXN3 and neurofi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…Our findings in aged homozygous Q84/Q84 mice reveal synonymous trends, with significantly increased blood NfL levels at late-stage disease. Although these mice showed no correlation between age and serum NfL, this result is consistent with studies on patients with SCA3 demonstrating decreased magnitude of blood NfL increases over time ( Li et al, 2019 ; Peng et al, 2022 ; Wilke et al, 2020b ; Faber et al, 2023 preprint). This suggests a plateau effect, i.e.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Our findings in aged homozygous Q84/Q84 mice reveal synonymous trends, with significantly increased blood NfL levels at late-stage disease. Although these mice showed no correlation between age and serum NfL, this result is consistent with studies on patients with SCA3 demonstrating decreased magnitude of blood NfL increases over time ( Li et al, 2019 ; Peng et al, 2022 ; Wilke et al, 2020b ; Faber et al, 2023 preprint). This suggests a plateau effect, i.e.…”
Section: Discussionsupporting
confidence: 89%
“…Studies in patients with SCA3 have demonstrated trends for NfL increases between the pre-ataxic stage and symptomatic ataxia onset ( Wilke et al, 2020b ; Li et al, 2019 ; Peng et al, 2022 ; Faber et al, 2023 preprint), and stably increased NfL levels during the symptomatic ataxic phase. These trends are reflective of increased neuronal turnover during the pre-ataxic phase and stably increased neuronal turnover during the symptomatic ataxic phase ( Wilke et al, 2020b ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…SCA7 ataxic individuals have a higher level of expansion compared to premanifest individuals. Until now, the accumulation of the disease protein has been used as a biomarker in Huntington disease or SCA3; 29 , 30 the EI described here in SCA7 could be used to distinguish affected individuals for trial enrollment purposes. A study in a larger group would strengthen these data.…”
Section: Discussionmentioning
confidence: 99%